2003
DOI: 10.4049/jimmunol.170.5.2638
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Proteinase-Activated Receptor 1 Expression in Astrocytes During HIV Encephalitis

Abstract: Proteinase-activated receptor 1 (PAR-1) is a G protein-coupled receptor that is activated by thrombin and is implicated in the pathogenesis of inflammation. Although PAR-1 is expressed on immunocompetent cells within the brain such as astrocytes, little is known about its role in the pathogenesis of inflammatory brain diseases. Herein, we investigated PAR-1 regulation of brain inflammation by stimulating human astrocytic cells with thrombin or the selective PAR-1-activating peptide. Activated cells expressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 84 publications
3
92
0
Order By: Relevance
“…All mouse primer sequences were established previously (Overbergh et al, 1999;Sun et al, 2001), except for A2aAR (5Ј-CGCCATCCCATTCGCCATCAC-3Ј and 5Ј-CCTTCGCCTTCATACCCGTCACCA-3Ј), A3AR (5Ј-GCCTTCGC-ATGTGGTATCAGTAAA-3Ј and 5Ј-GAAGGGCAGAGTCCGTGGT-AATC-3Ј), and MMP-12 (5Ј-TTTCTTCCATATGGCCAAGC-3Ј and 5Ј-GGTCAAAGACAGCTGCATCA-3Ј). All human primer sequence were reported previously (Boven et al, 2003), except for A1AR (5Ј-CCCCCTCGCCATCCTCATCA-3Ј and 5Ј-GCCCGCTCCACCGCA-CTC-3Ј) and MMP-12 (5Ј-GGGGCCCGTATGGAGGAAACA-3Ј and 5Ј-CACGGGCAAAAACCACCAAAATG-3Ј). Semiquantitative analysis was performed by monitoring in real-time the increase of fluorescence of the SYBR-green dye (Molecular Probes) on a Bio-Rad (Hercules, CA) i-Cycler.…”
Section: Methodsmentioning
confidence: 99%
“…All mouse primer sequences were established previously (Overbergh et al, 1999;Sun et al, 2001), except for A2aAR (5Ј-CGCCATCCCATTCGCCATCAC-3Ј and 5Ј-CCTTCGCCTTCATACCCGTCACCA-3Ј), A3AR (5Ј-GCCTTCGC-ATGTGGTATCAGTAAA-3Ј and 5Ј-GAAGGGCAGAGTCCGTGGT-AATC-3Ј), and MMP-12 (5Ј-TTTCTTCCATATGGCCAAGC-3Ј and 5Ј-GGTCAAAGACAGCTGCATCA-3Ј). All human primer sequence were reported previously (Boven et al, 2003), except for A1AR (5Ј-CCCCCTCGCCATCCTCATCA-3Ј and 5Ј-GCCCGCTCCACCGCA-CTC-3Ј) and MMP-12 (5Ј-GGGGCCCGTATGGAGGAAACA-3Ј and 5Ј-CACGGGCAAAAACCACCAAAATG-3Ј). Semiquantitative analysis was performed by monitoring in real-time the increase of fluorescence of the SYBR-green dye (Molecular Probes) on a Bio-Rad (Hercules, CA) i-Cycler.…”
Section: Methodsmentioning
confidence: 99%
“…The brain tissues used in these experiments have been described in previous reports (30,31) and were obtained from the AIDS Brain Bank at St. Paul's Hospital (Vancouver, Canada) and the Neurovirology Laboratory Brain Bank at the University of Calgary. Samples represented frontal white matter that was collected at autopsy from all experimental groups and stored at Ϫ80°C.…”
Section: Cells and Tissuesmentioning
confidence: 99%
“…Primary Abs were detected with biotinylated goat anti-rabbit or biotinylated goat anti-mouse Abs, followed by avidin-biotin-peroxidase complexes. Peroxidase activity was detected by diaminobenzidine or alkaline phosphatase (Vector Laboratories, Burlingame, CA), as previously reported (31). Hematoxylin was used to counterstain sections to assist in identifying cells expressing RON.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…PAR-1 has also been implicated in the pathogenesis of neuroinflammatory/degenerative disorders (13,14). Previous studies from our group demonstrated an important role for astrocytic PAR-1 up-regulation and activation in the neuropathogenesis of HIV-1 infection (15), characterized by neuroinflammation and neuronal injury. Indeed, neuronal dysfunction and death likely underlie the motor, behavioral, and cognitive impairments that are present among patients with HIV-associated dementia (HAD), which usually becomes manifest during AIDS.…”
mentioning
confidence: 99%